Mevalonate Diphosphate Decarboxylase MVD/Erg19 Is Required for Ergosterol Biosynthesis, Growth, Sporulation and Stress Tolerance in Aspergillus oryzae - Sun, Yunlong; Niu, Yali; Huang, Hui; He, Bin; Ma, Long; Tu, Yayi; Tran, Van-Tuan; Zeng, Bin; Hu, Zhihong (Frontiers in Microbiology, 2019)
Mevalonate diphosphate decarboxylase (MVD; EC 4.1.1.33) is a key enzyme of the mevalonic acid (MVA) pathway. In fungi, the MVA pathway functions as upstream of ergosterol biosynthesis, and MVD is also known as Erg19. Previously, we have identified AoErg19 in Aspergillus oryzae using bioinformatic analysis. In this study, we showed that AoErg19 function is conserved using phylogenetic analysis and yeast complementation assay. Quantitative reverse transcription–PCR (qRT-PCR) indicated that AoErg19 expression changed in different growth stages and under different forms of abiotic stress. Subcellular localization analysis showed that AoErg19 was located in the mitochondria. Overexpression of AoErg19 decreased the ergosterol content in A. oryzae, which may due to the feedback-mediated downregulation of AoErg8. Consistent with the decrease in ergosterol content, both AoErg19 overexpression and RNAi strains of A. oryzae are sensitive to abiotic stressors, including ergosterol biosynthesis inhibitor, temperature, salt and ethanol. Thus, we have identified the function of AoErg19 in A. oryzae, which may assist in genetic modification of MVA and the ergosterol biosynthesis pathway.